Improving Water Security for Sustaining Livelihoods and Growth in Tanzania - Hirji, Rafik; Davis, Richard; Brown, Francis Ato (World Bank, Washington, DC, 2012)
The Tanzania Water Resources Assistance Strategy (TWRAS) illustrates that food security, energy security, environmental security, health security, industrial security, and social and economic security all hinge directly or indirectly on water security. The cooperative management and development of rivers, lakes, and aquifers shared with other nations also have significant implications for national security. The TWRAS has guided the preparation of the second generation of the Bank's programmatic and sector wide investments, emphasizing improved linkages between programmatic elements. It argues for an integrated investment program supported by a more empowered, better resourced, and accountable governance regime. The strategy establishes that equitable and sustainable management and development of water resources is a fundamental prerequisite for achieving the outcomes of the national strategy for growth and reduction of poverty, which identifies the following intended poverty reduction outcomes: growth and reduction of income poverty; improved quality of life and social well-being; and good governance and accountability.